1991
DOI: 10.1002/jemt.1060170405
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and pathophysiology of the human spermatozoon: The role of electron microscopy

Abstract: In this article, the major contributions of electron microscopy to the present understanding of the physiology and pathophysiology of the human spermatozoon are reviewed. The ultrastructural organization of sperm organelles playing a significant role for cell function and, therefore, for the reproductive process is described. Also, the major abnormalities and defects of the various organellar systems and how they impair the reproductive function and/or the viability of the cell are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 92 publications
0
26
1
2
Order By: Relevance
“…High numbers indicate an intact surface or slight damage (4 and 3 points) and low numbers indicate severe damage (2 points) or an absent acrosome (1 point). While in a fully differentiated human spermatozoon, the acrosome covers the anterior four-fifths of the nucleus (Zamboni, 1991), an incomplete or absent acrosome was found in 60% of untreated sperms. Acrosomai abnormalities can be either acquired or congenital (Zamboni, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…High numbers indicate an intact surface or slight damage (4 and 3 points) and low numbers indicate severe damage (2 points) or an absent acrosome (1 point). While in a fully differentiated human spermatozoon, the acrosome covers the anterior four-fifths of the nucleus (Zamboni, 1991), an incomplete or absent acrosome was found in 60% of untreated sperms. Acrosomai abnormalities can be either acquired or congenital (Zamboni, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Sperm washing resulted in improved sperm quality with the amount of acrosomal abnormalities remaining unchanged. Being involved in both capacitation and the ability of the sperm to penetrate the egg, the acrosome plays a key role in the reproductive process (Zamboni, 1991). The number of characteristics examined in our own SEM study allowed statistical evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth evaluation of semen quality by transmission electron microscopy (TEM) can improve the diagnosis of male sub fertility and can give substantial information about the fertilizing competence of male gamete [Kupker et al 1998, Jian-Jun andYue-Min 2004;Takeuchi et al 2004]. It has been reported that normal spermatozoa ultrastructure correlated with positive IVF results [Mashiach et al 1992;Zamboni 1991;Baccetti et al 1995;Carbone et al 1998;Bartoov et al 1999]. TEM evaluation of sperm can also identify potentially inheritable genetic disorders (e.g., primary ciliary dyskinesia, Kartagener's syndrome), providing valuable information for couples contemplating ICSI [Carbone et al 1998;Lamb 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not all conditions characterized by ineffective motility are caused by spermatogenesis defects. On the contrary, impairment of motility may be induced by several factors: environment (immunological factor, hyperviscosity, alteration of secretory gland function, reproductive male tract infections), disturbance of flagellar motility regulation (Turner, 2003) and acquired or primary flagellar anomaly (Zamboni, 1991;Chemes et al, 1998).…”
Section: Asthenozoospermia As the Sole Sperm Alteration Or Associatedmentioning
confidence: 99%